A Case Study: Management and Exploitation of the Nuclear Decommissioning Agency Geoscience Data Archive. Issue 1 (3rd July 2018) - Pinnick, Jaana; Riddick, Andrew; McLaverty, Robert; Baker, Garry
ABSTRACT: The British Geological Survey (BGS) is responsible for managing a major geoscience data archive on behalf of the UK Nuclear Decommissioning Authority (NDA). Much of this geological data was captured during the 1990s and early 2000s using now obsolete software and data formats. This data asset remains an important resource for the NDA and the wider scientific community. The NDA wishes to ensure the data remain accessible and usable for many decades into the future. BGS has been working closely with Radioactive Waste Management (RWM), a wholly owned subsidiary of the NDA, on a program of data management and digital continuity measures to ensure the long-term usability of the data. This article describes some of the challenges and outlines the approaches we have taken to address these issues.